Bending behavior of steel-UHPC composite bridge deck based on epoxy adhesive - Li, Baojun; Jiang, Jinlong; Deng, Zhiheng; Zhou, Heying; Wang, Haicui; Jiang, Haoting; Cao, Yidong (Frontiers in Materials, 2022)
Using ultra-high performance concrete (UHPC) as the pavement layer of orthotropic steel deck (OSD) can greatly enhance the rigidity of the bridge deck to solve the fatigue cracking of the steel deck and the damage to the pavement layer. However, the thin UHPC layer limits the extensive use of the short stud connector. In this study, three types of interfaces were designed by introducing different additives into the epoxy matrix, and the shear properties of each interface and short stud connector were compared. Then, through the bending test of the composite bridge deck, the influence of short stud connectors and optimized interface on the bending property of the composite bridge deck was analyzed. Finally, the mechanical behavior of the interface in the composite bridge deck is discussed based on the finite element model. The results show that the ultimate load of the composite bridge deck with the optimized interface is reduced by 21.5 % compared with the composite bridge deck with the short stud connector. However, the composite bridge deck with the optimized interface has higher bending stiffness before failure and is less affected by cyclic loading. Moreover, the composite bridge deck with the optimized interface is unsuitable for cyclic loading when the defect area reaches 30%. Finally, based on the cohesive zone model, the numerical simulation of the composite bridge deck with the optimized interface is successfully realized, and the applicability of the interface in the composite bridge deck is verified.